Penerapan Model Problem Based Learning Terintegrasi STEM terhadap Keterampilan Berpikir Kritis pada Materi Hukum Newton: Implementation of STEM Integrated Problem Based Learning Model on Critical Thinking Skills in Newton's Law Material - Jeffrey Payung Langi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Critical thinking skills are one of the primary abilities students must master in the 21st century. One of the materials that requires this skill is Newton's Law, which is often a challenge in learning physics. Newton's Law is an essential topic in physics that students usually consider difficult. The research focused on the effect of implementing the Problem-Based Learning (PBL) model integrated with STEM on students' critical thinking skills in Newton's Law material. The STEM-based PBL approach can be proven to hone students' analytical and critical thinking skills. However, although the benefits of PBL and STEM have been widely discussed, studies that integrate both in Newton's Law material are still minimal. The approach is quasi-experimental with a pretest-posttest control group technique involving two classes: experimental (PBL integrated with STEM) and control (conventional approach). Data was generated through pretest-posttest to assess students' critical thinking skills. This approach provides opportunities for students to apply concepts in real life through exploration and problem-solving. The study results indicate a significant difference between the experimental and control classes with a p-value of 0.036 (p <0.05) and a d-value of 0.53, so it is included in the moderate influence category. Thus, the integrated PBL approach with STEM effectively improves students' critical thinking skills in Newton's Law material.